(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
With broadly similar case formation — diverse stems, but similar endings. Sanskrit also has a corresponding class (although not commonly termed as third), in which the so-called basic case endings are applied very regularly